El derecho a ser padres: Rompiendo los paradigmas del derecho de familia, bajo una concepción legal o ilegal - Samaniego Quiguiri, Delia Paulina; Bonilla-Morejón, Diego Marcelo; Martínez-Tapia, José David; Navarrete-Valladolid, María Isabel; Solis-Miranda, Diego Fernando; Zambrano-Villacrés, Dayana Estefanya; Bucheli-Cárdenas, Cristhian Marcelo; Murillo-Ramos, Franklin Remigio; Erazo-Zela, Víctor Hugo; Guala-Agualongo, Carlos Javier (Editorial Grupo AEA, 2024)
Talking about the right to be parents is a reality that is not always recognized as such, but which, from a subjective point of view, goes beyond a simple whim. It is a game of complementarity aimed at the formation of a family. In Ecuador, surrogacy lacks regulation within the legal framework. Despite attempts to regulate these procedures of human reproduction, no consensus has been reached among those in charge of creating laws. This has generated divergent criteria among legislators, resulting in a lack of conclusions and allowing this type of procedure to continue without guaranteeing the best interests of the minor or the surrogate parents. This work addresses the importance of the right to be parents from a perspective that can be considered illegal in some cases and legal in others, adoption being part of the latter category. Adoption is characterized as a legal institution that facilitates the establishment of bonds of affection between parents who lack children and vice versa. For those who wish to have a child, it is essential to comply with the requirements established by current legislation, since mere desire is not enough. In this context, both surrogacy and adoption are presented as mechanisms that enable individuals and couples to achieve parenthood, although they differ in their processes and circumstances. The objective of this text is to offer a clear understanding of the mechanisms associated with each process, breaking paradigms in the field of family law and highlighting that both lead to the opportunity to form a family, which is the basis of the social fabric.